Unique Pattern of Hypertension Fingerprints - Syamsurizal, S.; Sudarni; Badriyya, Elsa; Putri, Sintia (Genetikawan Muda Indonesia, 2022)
The fingerprint pattern (dermatoglyphics) of each individual is not the same. Fingerprint patterns are often used as an identification tool in criminal cases and disease diagnosis. Fingerprint patterns for health diagnosis are usually diseases caused by genetic factors, for example hypertension. The purpose of this study was to describe the characteristics of fingertip dermatoglyphics of hypertension patients. The research sample was 60 people consisting of 30 people with hypertension who visited the DR. M. Djamil Padang and controls 30 non-hypertension (normal) people from Biology FMIPA UNP students. Simple random sampling. The research variables are tendril patterns on the fingertips. The Chi-square test was used to analyse the tendril pattern data of hypertension patients. The results showed that the arch fingerprint pattern is a unique character in hypertensive patients.